Expression and clinical implications of leucine‐rich repeat containing 15 (LRRC15) in osteosarcoma. Issue 11 (19th September 2020) - Cui, Juncheng; Dean, Dylan; Wei, Ran; Hornicek, Francis J.; Ulmert, David; Duan, Zhenfeng
Abstract: Leucine‐rich repeat containing 15 (LRRC15) is a member of the leucine‐rich repeat superfamily that is overexpressed in various cancers and associated with higher tumor grade and aggression. Despite its known tumorigenicity, its roles within osteosarcoma are unknown, prompting us to evaluate its expression and clinical significance within this rare yet aggressive cancer. Western blots showed differential expression of LRRC15 in the osteosarcoma cell lines MNNG/HOS, KHOS, 143B, MG63, Saos‐2, and U2OS. We additionally validated this positive expression, as well as sublocalization to the cell membrane, with immunofluorescence. A tissue microarray constructed from 69 osteosarcoma patient tissues was immunohistochemically stained for LRRC15 expression, stratified, and used for clinicopathological analysis. Publicly available databases on LRRC15 expression, including RNA sequencing data from the Therapeutically Applicable Research to Generate Effective Treatments on Osteosarcoma (TARGET‐OS) and the Gene Expression database of Normal and Tumor tissues 2 (GENT2) were also analyzed. We found 63 of the 69 (91.3%) patient tissues exhibited some degree of LRRC15 immunostaining, including no staining (6 of 69, 8.7%), 1+ staining (12 of 69, 17.4%), 2+ staining (25 of 69, 36.2%), and 3+ staining (26 of 69, 37.7%). The patients with osteosarcomas having elevated LRRC15 expression demonstrated comparatively increased metastasis, chemoresistance, and shorter 5‐year survival rates. Our analysis of the TARGET‐OS and GENT2 databases also showed increased LRRC15 gene expression in osteosarcoma. Taken together, our study supports LRRC15 as a prognostic biomarker and emerging therapeutic target in osteosarcoma.